Urinary phoretograms performed by capillary electrophoresis in dogs with chronic disease with or without Leishmania infantum infection - Navarro, Paula Fátima; Fernández-Barredo, Salceda; Gil, Laura (Frontiers in Veterinary Science, 2022)
Introduction The study of early markers to detect kidney malfunction has increased in recent years since serum markers, such as creatinine increase when there is a 75% loss of renal mass. Urinary capillary electrophoresis (UCE) is an available laboratory technique that provides an easily interpretable electrophoretic pattern. This pattern in our study has been divided into five fractions as it is done in serum: fraction 1 migrating in the albumin zone, fraction 2 in the alpha1-globulins zone, fraction 3 in the alpha2-globulins zone, fraction 4 in the beta-globulins zone, and fraction 5 in the gamma globulins zone. UCE can be useful in the early diagnosis of renal disease. Material and methods In this study, UCE was performed in dogs with azotemia and proteinuria due to chronic kidney disease (CKD) not related to Leishmania infantum (L. infantum) infection (G1, n = 11) and dogs with CKD related to L. infantum infection (G2, n = 17) and compared with reference intervals from healthy dogs (G0, n = 123), with the aim of comparing their phoretograms and assessing changes in the fractions of the phoretograms based on the health status of individuals. Results Fraction 2 was statistically augmented in dogs with CKD (G1) when compared with the healthy population (G0) and dogs infected by L. infantum (G2). Fraction 3 was statistically increased in dogs with CKD (G1) and dogs infected by L. infantum (G2) compared with G0. Fraction 4 was found to be statistically decreased in dogs with CKD (G1) and dogs infected by L. infantum (G2) compared with G0. Fraction 5 was statistically higher in dogs with L. infantum (G2) compared with G0 and dogs with CKD (G1). No statistical relationship was found between the protein to creatinine ratio and different fractions from the urinary phoretogram in the study population. No statistical relationship was found between serum and urine fractions in the study population. Discussion The results of the present study suggest that UCE is a promising non-invasive technique that might be used as a part of the diagnostic and follow-up in dogs with kidney disease due to different pathologies.